New two-way discrete frequency table with application to English Premier League data - Mohammed, M. B.; Zulkafli, H. S.; Ali, N.; Olaniran, O. R.; Ahmed, H. (Taylor Francis, 2022)
A bivariate discrete frequency table, one of the significant exploratory data analysis (EDA) tools, organizes data systematically. The existing frequency table is straightforward, but when the number of elements in the data is large enough, the table can be complicated. In this research, we proposed a new bivariate discrete frequency table by grouping the elements in each variable. The table can be constructed using the R code provided with the article. We described the table using simulations from the bivariate binomial distribution, bivariate Poisson distribution. Real data, obtained from the English Premier League website, is also used to illustrate the new table. The findings indicated that the proposed bivariate frequency table provides a better alternative when the number of elements is substantial and reveals the essential data features.